An Immune-Related Gene Pairs Signature for Predicting Survival in Glioblastoma - Wang, Sheng; Xu, Xia (Frontiers in Oncology, 2021)
Background: Glioblastoma (GBM) is the frequently occurring and most aggressive tumor of brain tumors. In the study, we constructed an immune-related gene pairs (IRGPs) signature to predict overall survival (OS) in GBM patients. Methods: We established IRGPs with immune-related gene matrix from the TCGA database (Training cohort). After screened by univariate regression analysis and LASSO regression analysis, IRGPs were subjected to multivariable Cox regression to develop an IRGPs signature. Then, the predicting accuracy of the signature was assessed with the area under the receiver operating characteristic curve (AUC) and validated the result with CGGA data (Validation cohort 1 and 2). Results: A ten IRGPs signature was established for predicting the OS of GBM patients. The AUC for predicting 1-, 3- and 5-year OS in Training cohort was 0.801, 0.901, and 0.964, respectively, in line with the AUC of Validation cohort 1 and 2 (Validation cohort 1 [1-year: 0.763; 3-years: 0.786; 5-years: 0.884]; Validation cohort 2 [1-year: 0.745; 3-years: 0.989; 5-years: 0.987]). Besides, survival analysis in three cohorts suggested that low-risk GBM patients had better clinical outcomes than high-risk patients. The univariate and multivariable Cox regression demonstrated that the IRGPs signature was an independent prognostic factor. Conclusions: We developed a novel IRGPs signature for predicting OS in patients with GBM.